A test for allelopathy of the invasive Cedrela odorata L. (Meliaceae: Magnoliidae) in Galapagos - Rivas Torres, María Gloria (2015)
Non-native plant species, especially in the Galapagos Islands, are considered to be one of the main threats to native organisms, ecosystems, human welfare and ecosystems worldwide. Following are the results of an experiment that was conducted to prove the potential inhibitory effects of the leaf and root extracts derived from the invasive Cedrela odorata L. (Meliaceae: Magnoliidae) tree on germination and growth of four native and four non-native species of the Galápagos archipelago. Experiments were set on the field using germination substrate for seeds, which along with seedlings of the eight species used for the experiment, were kept in the greenhouse of the Galápagos National Park (GNP). The effects of the extracts on germination and growth were compared against rainwater (control). Results showed that, although, overall the allelopathic influences were species specific for both germination and height patterns, individual species analysis revealed the extracts of C. odorata leaf and root caused a significantly negative effect on growth (height and dry weight) of the endemic Scalesia pedunculata, which is the main tree competitor of C. odorata in the Archipelago. These results may help to explain the dominance of C. odorata and the consequent exclusion of S. pedunculata in highly invaded area in Santa Cruz Island.